2010
DOI: 10.1097/pas.0b013e3181da7650
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Use of Antibody to Smoothelin in the Recognition of Muscularis Propria in Transurethral Resection of Urinary Bladder Tumor (TURBT) Specimens

Abstract: Accurate recognition of muscularis propria invasion by urothelial carcinoma is vital as it serves as a crossroad between conservative and aggressive clinical management. Recently, there has been attention to the hyperplastic pattern of muscularis mucosae which may mimic the muscularis propria. We have earlier shown that smoothelin, a marker of terminally differentiated smooth muscle cells, is relatively specific for muscularis propria (positive staining) and is variably negative to weak in muscularis mucosae. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 11 publications
(16 reference statements)
2
39
1
Order By: Relevance
“…Recently, attempts have been made to use immunohistochemistry (IHC) for smoothelin to differentiate between MM and MP in the bladder [10,11,[13][14][15]. These studies have reported strong expression of smoothelin in the MP contrasted to absent or weak expression in the MM.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, attempts have been made to use immunohistochemistry (IHC) for smoothelin to differentiate between MM and MP in the bladder [10,11,[13][14][15]. These studies have reported strong expression of smoothelin in the MP contrasted to absent or weak expression in the MM.…”
Section: Introductionmentioning
confidence: 97%
“…Despite the fact that vascular plexus is absent in MP, it can also be absent in MM, especially in transurethral resection of urinary bladder tumor (TURBT) specimens (10). Moreover, TURBT specimens of low quality and low quantity are not rare, leading to disorientation of the specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, TURBT specimens of low quality and low quantity are not rare, leading to disorientation of the specimens. There are topographical variations of the MP bundles in bladder trigone and at the insertion of the ureter (8,10). Trigonal MP extends more superficially and often shows gradual diminution of the bundle size as it extends to an almost suburothelial location.…”
Section: Introductionmentioning
confidence: 99%
“…83,86 However, it has not been widely used in practice because of its limitations. 87,88 PROSTATE Example 3: A 63-year-old man was diagnosed with Gleason 3 þ 3 adenocarcinoma, involving 5% of one core, 5 years earlier. He was subsequently treated with intensitymodulated radiotherapy.…”
Section: Roles Of Immunohistochemical Markers In Staging Of Bladder Cmentioning
confidence: 99%